[Rezension von: The rise of the early Christian intellectual] - Paget, James Carleton (The journal of ecclesiastical history, 2021)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0022046920001566/resource/name/firstPage-S0022046920001566a.jpg